Skin-on-a-Chip Device for Ex Vivo Monitoring of Transdermal Delivery of Drugs-Design, Fabrication, and Testing - Bence Lukács; Ágnes Bajza; Dorottya Kocsis; Attila Csorba; István Antal; Kristóf Iván; András József Laki; Franciska Erdő (MDPI AG, 2019)
To develop proper drug formulations and to optimize the delivery of their active ingredients through the dermal barrier, the Franz diffusion cell system is the most widely used in vitro/ex vivo technique. However, different providers and manufacturers make various types of this equipment (horizontal, vertical, static, flow-through, smaller and larger chambers, etc.) with high variability and not fully comparable and consistent data. Furthermore, a high amount of test drug formulations and large size of diffusion skin surface and membranes are important requirements for the application of these methods. The aim of our study was to develop a novel Microfluidic Diffusion Chamber device and compare it with the traditional techniques. Here the design, fabrication, and a pilot testing of a microfluidic skin-on-a chip device are described. Based on this chip, further developments can also be implemented for industrial purposes to assist the characterization and optimization of drug formulations, dermal pharmacokinetics, and pharmacodynamic studies. The advantages of our device, beside the low costs, are the small drug and skin consumption, low sample volumes, dynamic arrangement with continuous flow mimicking the dermal circulation, as well as rapid and reproducible results.